DEFENSE MECHANISM FOR CORRUPTION CONVICTS TO INCREASE MOTIVATION IN PARTICIPATING PERSONALITY DEVELOPMENT PROGRAMS IN CLASS IIA CORRECTIONAL INSTITUTION - Muhammad Fadlan Nugroho; Meitisa Vanya Simanjuntak (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study was conducted at the Class IIA Correctional Institution in Bengkulu to explore how inmates convicted of corruption (tipikor) experience their sentences from a psychological and personality development perspective. Using a qualitative approach, the findings reveal that inmates employ various defense mechanisms to cope with the pressures of incarceration. These mechanisms can be categorized into three types: mature, neurotic, and immature. Mature defense mechanisms such as sublimation, anticipation, suppression, and humor enable inmates to remain positive, active, and cooperative, particularly in participating in programs like religious activities, gardening, and social interaction. Neurotic mechanisms, including pseudo-altruism and undoing, are used to reduce inner conflict by engaging in helpful or religious behaviors. However, less adaptive (immature) mechanisms, such as projection, passive-aggression, and idealization, are also observed among some inmates, indicating that not all individuals are able to regulate their emotions effectively. The study concludes that understanding these psychological coping strategies is essential for developing more targeted and effective rehabilitation programs. This is particularly important for corruption offenders, who often come from relatively high social and educational backgrounds, requiring more nuanced and psychologically informed approaches to support their personal transformation and reintegration into society. Keywords: Defense Mechanism; Personality Development; Corruption Inmates